»Odin og Saga« genfundet. En Grundtvig-tekst fra 1810 - Lundgreen-Nielsen, Flemming (Grundtvig-Studier, 1979)
‘Odin and Saga’ Rediscovered. A Grundtvig manuscript from 1810 published by Flemming Lundgreen-Nielsen. ‘Odin and Saga’ was the name of a journal that never saw the light. The text published here is the one for which subscriptions were invited. Steen Johansen regretted its loss in his Bibliography of the Works of N.F.S. Grundtvig (vol I p. 50 and vol IV p. 11). It was found in 10 copies amongst the papers left by F.C. Sibbern and is here printed with an introduction and notes. The plan was to publish a journal of philosophy, poetry and history with 4 issues annually each of 190 pages. Sibbern was to contribute a prizewinning essay on the principle and nature of philosophy and another essay on the principle behind a philosophical ‘doctrine of happiness’ (eudaimonism). In addition there was to be ‘A historical character sketch of Schiller as poet’, ‘An inquiry into the freedom of the human soul’ and an essay ‘Concerning the moral principle’, the authors of which were not named. Lundgreen-Nielsen assumes that Sibbern and Grundtvig have drafted the journal together but finds that the finished product bears rather Grundtvig’s stamp in its mode of expression. History and poetry are considered from a universal, historical angle, and the section on philosophy does not touch on the relationship between that particular science and Christianity or theology. Grundtvig has not yet become the severe judge of the life of the spirit with a Bible in his hand. Lundgreen-Nielsen attributes the only limited interest in the project to its failure to make its mark as part of the national religious revival. The journal ‘Danne-Virke’ 1816- 19, on the other hand, gathered its diversified contents around the concept of Danishness, most likely owing to Grundtvig’s own development between 1810-20.